Pathology of nNOS-Expressing GABAergic Neurons in Mouse Model of Alzheimer's Disease. (1st August 2018) - Choi, Seungho; Won, Je-Seong; Carroll, Steven L.; Annamalai, Balasubramaniam; Singh, Inderjit; Singh, Avtar K.
Graphical abstract: Highlights: APPSwDI transgenic mice develop early loss of GAD67 expression in CA1 of hippocampus. GAD67 + neurons exhibit high basal expression of nNOS and nitrosative stress. These neurons are highly vulnerable to Aβ due to the high intrinsic nitrosative stress. The loss of GAD67 + neurons correlates with cognitive and neuropsychiatric deficits. These suggest a role of nitrosative stress in of Alzheimer's GABAergic pathology. Abstract: Alzheimer's disease (AD) is the most common form of dementia that is often accompanied by mood and emotional disturbances and seizures. There is growing body of evidence that neurons expressing γ-aminobutyric acid (GABA) play an important role in regulation of cognition, mood, and emotion as well as seizure susceptibility, but participation of GABAergic neuronal pathology in Alzheimer's disease (AD) is not understood well at present. Here, we report that transgenic mice expressing human amyloid precursor protein Swedish–Dutch–Iowa mutant (APPSweDI ) exhibit early loss of neurons expressing GAD67, a GABA-synthesizing enzyme, in advance of the loss of pyramidal neurons in hippocampal CA1 region. The loss of GAD67 + neurons in APPSweDI mice accompanied with decreased spatial cognition as well as increased anxiety-like behaviors and kainic acid-induced seizure susceptibility at early phase. In the hippocampal CA1 region, GAD67 + neurons expressed high basal levels of neuronal nitric oxide synthase (nNOS) and nitrosative stress (nitrotyrosine). Similarly, GAD67 + neurons in primary cortical and hippocampal neuron cultures also expressed high basal levels of nNOS and degenerated in response to lower Aβ concentrations due to their high basal levels of nitrosative stress. Given the role of GABAergic neurons in cognitive and neuropsychiatric functions, this study reports the role of nNOS-mediated nitrosative stress in dysfunction of GABAergic neurons and its potential participation in early development of cognitive and neuropsychiatric symptoms in AD.